CO2 emissions in Indonesia: The role of urbanization and economic activities towards net zero carbon - Dyah Maya Nihayah; Izza Mafruhah; Lukman Hakim; Suryanto Suryanto (Economies, 2022)
This study aims to analyze the nexus between CO2 emissions, urbanization, and economic activity, as well as identify whether the pollution haven hypothesis is proven in Indonesia. It utilized time series data of Indonesia during the 1971-2019 period. Furthermore, the vector error correction model (VECM) was used to determine the long-run and short-run interplay using cointegration and Granger causality approaches. The empirical results showed the pollution haven hypothesis occurred in Indonesia. A long-term relationship with CO2 emissions was observed from the model. In addition, unidirectional causality occurred from urbanization, economic growth, exports, and foreign direct investment to CO2 emissions in the short term. It was concluded that the achievement of the Paris Agreement will be successful when the committed countries are courageous in transforming their economy. However, major adjustments are needed, where all parties need to have the same vision towards net zero carbon.
Keywords: 330; CO2 emissions; economic activities; net zero carbon; urbanization